Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/iop.0000000000000437
|View full text |Cite
|
Sign up to set email alerts
|

Axial Globe Position Measurement

Abstract: Purpose Identify a reproducible measure of axial globe position (AGP) for multicenter studies of patients with thyroid eye disease (TED). Methods This is a prospective, international, multicenter, observational study in which 3 types of AGP evaluation were examined: radiologic, clinical, and photographic. In this study, computed tomography (CT) was the modality to which all other methods were compared. CT AGP was measured from an orthogonal line between the anterior lateral orbital rims to the cornea. All CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
4
18
1
Order By: Relevance
“…CT also correlated well with HE. Both observations are compatible with those of previous studies [6][7][8]16].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…CT also correlated well with HE. Both observations are compatible with those of previous studies [6][7][8]16].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, accuracy remained unchanged as the degree of proptosis increased. Previous studies have yielded inconsistent results in this regard: some have found accuracy to be negatively associated with the degree of proptosis [2,17], while others have not [8]. e high levels of reliability and reproducibility observed in this study (ICC � 0.93 for clinical measurements; ICC � 0.95 for radiological measurements) match the results of several other studies [3,4,16].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations